2004
DOI: 10.1093/jee/97.3.741
|View full text |Cite
|
Sign up to set email alerts
|

Altered Physiology in Worker Honey Bees (Hymenoptera: Apidae) Infested with the Mite Varroa destructor (Acari: Varroidae): A Factor in Colony Loss During Overwintering?

Abstract: The ectoparasitic mite Varroa destructor (Anderson & Trueman) is the most destructive pest of the honey bee, Apis mellifera L., in Europe and the United States. In temperate zones, the main losses of colonies from the mites occur during colony overwintering. To obtain a deeper knowledge of this phenomenon, we studied the mites' impact on the vitellogenin titer, the total protein stores in the hemolymph, the hemocyte characteristics, and the ecdysteroid titer of adult honey bees. These physiological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
4
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(191 citation statements)
references
References 33 publications
7
172
4
8
Order By: Relevance
“…Although vitellogenin dynamics are complicated (Amdam et al, 2004b), the observed down regulation of vitellogenin supports a possible accelerated behavioural maturation of these bees.…”
Section: Infested and Non-infested Newly Emerged Bees (Experiments 2)mentioning
confidence: 63%
See 1 more Smart Citation
“…Although vitellogenin dynamics are complicated (Amdam et al, 2004b), the observed down regulation of vitellogenin supports a possible accelerated behavioural maturation of these bees.…”
Section: Infested and Non-infested Newly Emerged Bees (Experiments 2)mentioning
confidence: 63%
“…Additionally, high vitellogenin titers keep juvenile hormone levels low, thereby slowing behavioural maturation to foragers and potentially initiating the production of long-lived winter bees (Doke et al, 2015;Fluri et al, 1982). Previous studies have found that parasitization with Varroa produced workers that accumulate significantly fewer haemolymph proteins, including vitellogenin (Amdam et al, 2004b). Other studies found that Fig.…”
Section: Overlap Between the Three Deg Lists And Nurse/forager Genesmentioning
confidence: 99%
“…The dotted line exemplifies the investment in a bee that receives little or no proteinacious jelly after emergence. The dynamics match the relative vitellogenin concentrations of the bees accurately (e.g., Engels and Fahrenhorst, 1974;Fluri et al, 1982;Amdam et al, 2004a).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, flight is vital for foraging success as foraging for nectar and pollen sometimes involves several hours of flying a day and carrying heavy loads [14,18]. Negative effects on foraging performance may reduce pollen availability in the colony (as suggested by Wolf et al [16]), which reduces the number of reared bees [19], weakens newly hatched bees by reduced body mass and protein content [20,21], and induces precocious foraging [22,23]. A reduced food-collecting ability due to multiple stressors may ( partly) prevent the coping mechanism of precocious foraging, while the purpose of precocious foraging is to replenish the colony resources.…”
Section: Introductionmentioning
confidence: 99%